Monitoring and Evaluation of Commercial Cookery Training Practices - Helvy Yunida; Afandi Ismail; Dinny Devy; Iva Sarifah (East Asian Journal of Multidisciplinary Research, 2023)
Commercial cooking training is training in cooking techniques, so that someone can be competent in cooking. Alumni trainees can be independent by having their own business or using a certificate from BNSP to apply for jobs according to the competence of the type of work. The Purpose of Monitoring and Evaluation of Commercial Cookery Training Practices at the Bekasi Vocational and Productivity Centre. This research method uses a descriptive method with a quantitative approach. The results of the study obtained good results. The instructor is in accordance with the competence they have. Chef's education has passed a competency test and has attended the Training of the Trainer in accordance with the material that will be given to participants. Instructors have competencies that are in accordance with standardized participant competencies and trainees get the desired and needed commercial cooking competitions in today's era.